The impact of chirality on the analysis of alkaloids in plant - Ngoc-Van Thi Nguyen; Kim-Ngan Huynh Nguyen; Kien Trung Nguyen; Kyeong Ho Kim; Hassan Y. Aboul-Enein (Pensoft Publishers, 2021)
Most of the alkaloids are chiral compounds and are clinically administered as the racemic mixture, even though its enantiomers have been known to exert different pharmacological activity. The determination of the enantiomeric composition of alkaloid-containing plants is subject to severe attention from pharmacological and toxicological points of view. This review gives an overview of the chiral analysis of alkaloids that were used in theoretical studies and applications for plants in recent years.